2012
DOI: 10.2478/v10181-011-0119-3
|View full text |Cite
|
Sign up to set email alerts
|

Suppressive effect of electromagnetic field on analgesic activity of tramadol in rats

Abstract: The electromagnetic fields (EMFs) have been shown to alter animal and human behavior, such as directional orientation, learning, pain perception (nociception or analgesia) and anxiety-related behaviors. The aim of this study was to evaluate the influence of electromagnetic fields of high-frequency microwaves on pain perception and anti-nociceptive activity of tramadol (TRAM) -analgetic effective in the treatment of moderate to severe acute and chronic pain states.Electromagnetic fields exposures of a)1500 MHz … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Previous studies using subjective scales or reflex responses in the hot plate paradigm suggested contradictory RF-EMF effects on thermal sensitivity [ 13 , 15 , 29 , 30 ]. Here, RF-EMF effects on thermal sensitivity were assessed for the first time in an operant paradigm in the rat.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies using subjective scales or reflex responses in the hot plate paradigm suggested contradictory RF-EMF effects on thermal sensitivity [ 13 , 15 , 29 , 30 ]. Here, RF-EMF effects on thermal sensitivity were assessed for the first time in an operant paradigm in the rat.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, one may hypothesize that local skin thermal sensitivity was modulated through the chemical mediators influencing the higher-order midbrain regions controlling pain perception. Indeed, some studies suggested that cortisol release, central catecholamine or opioid peptide (endorphin) were influenced by RF-EMF exposures [ 15 , 16 , 17 , 18 , 35 , 36 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous studies we concluded that: -High frequency electromagnetic fields of 1500 MHz and 1800 MHz, when applied alone, did not influence pain perception threshold to thermal stimuli. It did, however, account for an unwanted effect -the diminishing analgesic action of tramadol [10]. -Electromagnetic fields exposure of 1800 MHz frequency and 20 V/m intensity, which is similar to cell phones, did not markedly influence the nociceptive threshold to thermal stimuli, although it did transiently decrease analgesic efficacy of tramadol in rats with complete Freund's adjuvant-induced paw inflammation [11].…”
Section: Introductionmentioning
confidence: 99%
“…It did, however, account for an unwanted effect -the diminishing analgesic action of tramadol [10]. -Electromagnetic fields exposure of 1800 MHz frequency and 20 V/m intensity, which is similar to cell phones, did not markedly influence the nociceptive threshold to thermal stimuli, although it did transiently decrease analgesic efficacy of tramadol in rats with complete Freund's adjuvant-induced paw inflammation [11]. In the last study [12] we recorded interesting findings for the groups of rats receiving tramadol and, concurrently, being exposed to an electromagnetic field.…”
Section: Introductionmentioning
confidence: 99%